An investigation into the insect ecology of citrus orchards, with special reference to citrus mussel scale (Lepidosaphes beckii newm.) - Carnegie, Alistair John Michael (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1955)
In the course cf the last fifteen years the general lnsect ecology of citrus orchards in the Eastern Cape has provided the subject matter of four theses presented for the degree of M.Sc. of Rhodes University. The false codlin moth, Argyroploce leucotreta Meyr., formed the subject of a thesis by Horne in 1939. Then in 1941 the same insect formed the subject matter of a thesis by Harris. The general ecology of a citrus orchard, with special regard to the biological control of citrus red scale, Aonidiella aurantii Mask., was the subject matter of Whitehead's thesis in 1948. This was a much more general investigation than the preceding two theses, and touched on many more aspects of citrus ecology. Another thesis dealing with more general citrus ecology was that of Smithers in 1953.
Keywords: Citrus -- Diseases and pests -- South Africa -- Eastern Cape; Lepidosaphes